Endovascular treatment of the ascending aorta: new frontiers for thoracic endovascular aneurysm repair? - Klonaris, Chris; Georgopoulos, Sotirios; Katsargyris, Athanasios (Journal of Thoracic Disease, 2016)
Pathology involving the ascending aorta has been traditionally treated with open surgery. Despite continuous improvement in the operative technique and perioperative care, mortality and morbidity of open surgery for type A aortic pathology remain considerable (1,2). Complications are mainly related to the use of cardiopulmonary bypass, while the risk for neurocognitive alterations should be also considered (3). Less invasive endovascular techniques could, at least theoretically, improve the results of ascending aortic repair.